2017
DOI: 10.18632/oncotarget.23301
|View full text |Cite
|
Sign up to set email alerts
|

Apancreatic pigs cloned using Pdx1-disrupted fibroblasts created via TALEN-mediated mutagenesis

Abstract: Pancreatic and duodenal homeobox 1 (PDX1) plays a crucial role in pancreas development, β-cell differentiation, and maintenance of mature β-cell function. In this study, we designed a strategy to produce PDX1-knockout (KO) pigs. A transcription activator-like effector nuclease (TALEN) pair targeting exon 1 of the swine PDX1 gene was constructed. Porcine fetal fibroblasts (PFFs) were transfected with the TALEN plasmids plus a surrogate reporter plasmid. PDX1-mutated PFFs were enriched by magnetic separation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…Previous research has revealed that disruption of the PDX1 gene in pigs has lethal effects and PDX1 biallelic mutants showed severe health problems caused by the pancreatic agenesis, including growth retardation, dehydration, severe diarrhea, and vomiting (Kang et al, 2017). In this study, we observed that piglets carrying PDX1 biallelic mutation similarly showed severe health problems and died within 2 days of birth.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous research has revealed that disruption of the PDX1 gene in pigs has lethal effects and PDX1 biallelic mutants showed severe health problems caused by the pancreatic agenesis, including growth retardation, dehydration, severe diarrhea, and vomiting (Kang et al, 2017). In this study, we observed that piglets carrying PDX1 biallelic mutation similarly showed severe health problems and died within 2 days of birth.…”
Section: Discussionmentioning
confidence: 99%
“…In the previous study, PDX1 ‐modified pigs have been generated by SCNT, which strategy is commonly used to generate mutant pigs (Kang et al, 2017). Although SCNT enables to generate mutant pigs carrying desired mutations, the use of this technique is associated with small litter sizes, low viability, and abnormal epigenetic regulation of resulting offsprings (Kurome et al, 2013; Wan et al, 2016; Zhao, Whyte, & Prather, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our previous study (Matsunari et al, 2013), we demonstrated that an apancreatic phenotype in pigs could be achieved by overexpressing the mouse Pdx1-Hes1 transgene. In this study, we knocked out porcine endogenous PDX1 gene, based on previous reports demonstrating apancreatic phenotype caused by Pdx1 À/À mutation in rodents (Jonsson et al, 1994;Kobayashi et al, 2010;Offield et al, 1996) and pigs (Kang et al, 2017).…”
Section: Apancreatic Phenotype Generated By Pdx1-ko and Restoration Omentioning
confidence: 99%